Independent and combined effects of antibiotic stress and EM microbial agent on the nitrogen and humus transformation and bacterial community successions during the chicken manure composting. (June 2022) - Zhao, Huaxuan; Li, Shangmin; Jiang, Yixiu; Wang, Danpin; Wang, Hongzhi; Dou, Xinhong
Graphical abstract: Highlights: EM microbial agent and antibiotics had an antagonistic effect on TN retention. EM microbial agent reduced the impacts of antibiotics on HS accumulation. Firmicutes were associated with HS conversion. Firmicutes, Actinobacteriota and Proteobacteria were related to nitrogen. Abstract: This study aimed to investigate the independent and combined effects of antibiotic and EM microbial agent on the nitrogen and humus (HS) transformations as well as the bacterial community successions during the chicken manure and rice husk composting. EM microbial agent accelerated the oxytetracycline (OTC) degradation, but slowed down the norfloxacin (NOR) degradation. OTC inhibited the TN retention and promoted the HS accumulation, both NOR and EM microbial agent inhibited the TN retention and HS accumulation, while EM microbial agent showed an antagonistic effect on TN immobilization with antibiotics and reduced the impacts of antibiotics on HS. Obvious bacterial community successions occurred. Firmicutes were related to HS transformation, while Firmicutes, Actinobacteriota and Proteobacteria were associated with nitrogen conversion. NOR promoted the transformations of NH4 + -N to NO3 — -N and FA to HA. The findings provided theoretical data for the recycle of antibiotic-contaminated manure and the efficient production of high-quality compost.